Minimum acceptable diet and associated factors among children aged 6-23 months in Ethiopia - Haimanot Abebe; Molla Gashu; Aynalem Kebede; Habtemariam Abata; Alex Yeshaneh; Haile Workye; Daniel Adane (BMC, 2021)
Abstract Introduction The health and growth of children less than two years of age can be affected by the poor quality of complementary foods and poor feeding practices even with optimal breastfeeding. In Ethiopia, empirical evidence on the minimum acceptable diet and its associated factors is limited. Therefore, this study was aimed to assess the level of minimum acceptable diet and its associated factors among children aged 6-23 months in Addis Ababa Ethiopia. Methods An institution-based Cross-sectional study was conducted among a total of 575 mother-child pairs. A simple random sampling technique was used to recruit participants. For infant and young child feeding practices, the data collection tools were adapted from world health organizations' standardized questionnaire which is developed in 2007. Data entry and analysis were performed using EPI data version 3.1 and SPSS version 20 respectively. Bivariable and multivariable logistic regression analyses were performed to determine predictor variables. Statistical significance was declared at p-value < 0.05. Result In this study, the level of minimum acceptable diet was found to be 74.6%.. About 90.6 and 80.2% of the children received minimum meal frequency and dietary diversity respectively. Having a husband secondary and above educational level [AOR = 4.789(95%CI:1.917-11.967)], being a housewife [AOR = 0.351(95% CI: 0.150-0.819)], having a history of more than three postnatal follow-ups [AOR = 2.616(95%CI:1.120-6.111], Having mothers age between 25 and 34 years [AOR = 2.051(95%CI:1.267-3.320)], being male child [AOR = 1.585(95%CI:1.052-2.388)] and having children age between 18 and 23 months [AOR = 3.026(95%CI:1.786-5.128)] were some of the factors significantly associated with a minimum acceptable diet. Conclusion In this study, the minimum acceptable diet among children aged 6-23 months was significantly associated with the educational status of the husband, mother's occupation, history of postnatal follow-up, age of the mother, sex of the child, and age of the child. Thus, attention should be given to educating the father, empowering mothers to have a job, promoting gender equality of feeding, and counseling on the benefit of postnatal care visits. In addition, the ministry of health should work on educating and advocating the benefit of feeding the recommended minimum acceptable diet to break the intergenerational cycle of malnutrition.